Asuhan Keperawatan pada Pasien Kanker Paru yang Menjalani Kemoterapi dengan Masalah Keperawatan Nyeri Kronis : Myalgia menggunakan Progressive Muscle Relaxation - Elfa Luvia Juliani; Dewi Damayanti; Pujiarto Pujiarto (Penerbit Goodwood, 2023)
Purpose: Lung cancer is a malignant tumor that grows abnormal cells and spreads to normal tissues in the human body. One of lung cancer treatment is chemotherapy with side effect is pain. Pain after chemotherapy, including myalgia or muscle pain, causes activity disruption and reduces productivity. Progressive muscle relaxation (PMR) is a non-pharmacological treatment to reduce myalgia pain in lung cancer patients undergoing chemotherapy. Progressive muscle relaxation is a deep muscle relaxation technique by relaxing and stretching muscles using 15 movements in 10-15 minutes. The aim of this study is to identify and analysis the nursing care of lung cancer patients undergoing chemotherapy with chronic pain nursing problems; myalgia using progressive muscle relaxation (PMR) in Paru Room, RSUD Dr. H. Abdul Moeloek Lampung Province. Method: The research method uses applied research with Pretest-Posttest Design. The research subjects used 2 people according to the inclusion criteria. The research instrument used observation sheets and standard operating procedures before and after the study with the Numeric Rating Scale (NRS) to measure the level of pain in both respondents before and after being given PMR for 5 days given 2 times a day in the morning and evening. Result: The results of this study Mrs. S average pain scale level 4.2 (moderate pain) to 3.6 (mild pain) and Mr.S average pain scale level 3.6 (mild pain) to 3 (mild pain). Conclusion: The conclusion of this study is that the application of PMR can reduce the level of myalgia pain in lung cancer patients undergoing chemotherapy.